Deciphering Markets and Money A Sociological Analysis of Economic Institutions - Gronow, Jukka (Helsinki University Press, 2020)
"During the last two decades, economic sociology has experienced a remarkable revival and has become one of the most innovative fields of sociological research. Shifts in economic policy worldwide have led to the increasing interest in the sociological analysis of economic phenomena and institutions by challenging traditional research questions and demonstrating the limits and problems inherent in standard economic thinking and reasoning. Jukka Gronow's book Deciphering Markets and Money solves the problem of the specific social conditions of an economic order based on money and the equal exchange of commodities. Gronow scrutinizes the relation of sociology to neoclassical economics and reflects on how sociology can contribute to the analyses of the major economic institutions. The question of the comparability and commensuration of economic objects runs through the chapters of the book. The author shows that due to the multidimensionality and principal quality uncertainty of products, markets would collapse without market devices that are either procedural, consisting of technical standards and measuring instruments, or aesthetic, relying on the judgements of taste, or both. In his book, Gronow demonstrates that in this respect, financial markets share the same problem as the markets of, wines, movies, or PCs and mobile phones, and hence offer a highly actual case to study their social constitution in the process of coming into being. Jukka Gronow is professor emeritus of sociology at Uppsala University, Sweden, and docent at the University of Helsinki, Finland. He has published on sociology of consumption, history of sociology and social theory."